Primary Cardiac Lymphoma: Lessons Learned from a Long Survivor - Baljit Singh; Randy Ip; Ahmed Ibrahim Al-Rajjal; Zyad Kafri; Ayad Al-Katib; Tarik Hadid (Case Reports in Cardiology)
Primary cardiac lymphoma (PCL) is a rare neoplasm that involves the heart, pericardium, or both. Patients with PCL have median survival of approximately 7 months. We report a 63-year-old woman with PCL treated with chemoimmunotherapy but relapsed 7 years later. She received automated implantable cardioverter-defibrillator (AICD) prophylactically shortly after the diagnosis. She presented with a breast recidive 7 years after initial diagnosis and died of relapsed small cell lung cancer. As many patients with PCL die early in the disease course due to life-threatening arrhythmias, preemptive implantation of AICD may improve mortality and prevent early death. Chemoimmunotherapy is effective in inducing remission in patients with PCL. Late and unusual pattern of relapse may be more frequent in patients with PCL and should be explored further. This case presents one of the longest surviving patients with PCL reported in the literature.